Bibliometric and visual analysis of diabetic keratopathy research: trends, collaborations, and future directions - Zhenyu, Wang; Jing, Gao; Tianhong, Wu (Frontiers in Medicine, 2024)
Purpose: Diabetic keratopathy has gained increasing attention due to advancements in diagnostic and therapeutic techniques a. This article presents a visual and bibliometric analysis to illustrate the knowledge network, research hotspots, trends, and potential future directions in this field. Methods: We retrieved articles published since 2000 from the Web of Science and analyzed the authors, institutions, countries, keywords, citations, and co-citations of these articles with VOSviewer and CiteSpace. Results: A total of 706 highly relevant articles were identified, with the United States, China and England as major contributors; the University of Manchester, Queensland University of Technology and Weill Cornell Medical - Qatar as key institutions; and Malik Rayaz, Efron Nathan and Ferdousi Maryam as prominent authors. High-citation articles have focused mainly on corneal confocal microscopy and diabetic peripheral neuropathy. Keywords form two clusters: one around complications, diabetes and cornea sensitivity, and another around corneal confocal microscopy and peripheral neuropathy. Conclusion: The identification of diabetic peripheral neuropathy via corneal confocal microscopy has been a major focus of research in this field, but the mechanisms underlying diabetic corneal neuropathy still require further investigation and breakthroughs.